Teachings on Writing Narrative Texts Through Teaching Clustering to Tenth Grade Students Nurul Huda Sukaraja High School - Bella Riska Awaliyah; agustina, eka; Zainuddin Afas, Muhamad (ENJEL: English Journal of Education and Literature, 2024)
Applying clustering methodologies to instruct narrative texts to tenth grade students at SMK Nurul Huda Sukaraja. The proof for this assertion is substantiated by the results of the Independent Sample t-test performed on the post-test scores of both the experimental and control groups. The calculated t-values were 5.954 and 5.984, with a significance (two-tailed) value of 0.000. Thus, it is feasible for the t-value to surpass the critical t-value of 2.021 when the degrees of freedom (df) are 49, given that the sample size (n) is 51. Furthermore, the two-tailed significance (Sig) value is below the preset significance limit (α) of 0.05. The Null Hypothesis is rejected and the Alternative Hypothesis (Ha) is upheld. There is a significant difference between students who are educated using the Write Narrative Text Clustering Technique and students who are guided using Write Narrative Text utilising the Clustering Technique. The results further demonstrated that the use of the Clustering Technique in the students' class resulted in a decrease in their writing challenges. By using the Clustering methodology, students may pinpoint the underlying source of writing problems and successfully address them. This strategy is very efficacious in augmenting the understanding of the topic matter.